“Snowed In” in Russia: A Historical Analysis of American and Russian Extradition and How the Snowden Saga Might Impact the Future - William C. Herrington (Washington University Journal of Law & Policy, 2015)
After Edward Snowden—an American citizen charged with theft and unauthorized communication of classified defense information (among other things)—was granted asylum by the Russian Federation, relations between the United States and Russia deteriorated rapidly. This Note analyzes the history of American and Russian extradition agreements and provides a sample extradition agreement that, if enacted prior to Russia’s asylum grant, may have altered the outcome.
Keywords: Edward Snowden; extradition; Russia; cybersecurity